Perawatan gigi impaksi anterior rahang atas pada remaja (The treatment of maxillary anterior impacted teeth in adolescent) - Herdi Eko Pranjoto; Jusuf Sjamsudin (Dental Journal (Majalah Kedokteran Gigi), 2005)
The incidence of impacted tooth in adolescent is usually found by oral surgeon or orthodontist during their sequence of treatments. The maxillary anterior teeth, especially canine and third lower molar are the most common impacted teeth found as the result of their eruption disturbances. The surgical technique principle is to facilitate the impacted tooth, so that it can be erupted by creating a window and take the bone obstructed surrounding the tooth crown surgically and afterward it is orthodontically tracted. In a case of third molar germ which is predicted to be impacted in mesio version position, germinectomy is preferred to prevent anterior mechanical drive during its development which may cause mal-alignment of the mandibular teeth. Germinectomy which is usually easier than odontectomy, the germ position, and less complication after the surgical intervention are three factors that should be considered in making decision.